The Effectiveness of the Integrated Community-Based Child Protection Program (PATBM) in Addressing Violence Against Children in Serang City - Mochamad Ulul adjmie; Rina Yulianti (International Journal of Social Sciences Review, 2026)
Serang City has experienced a continuous increase in reported cases of child violence since 2019. In response, Regional Regulation (Perda) No. 7 of 2013 concerning the Protection of Women and Children was enacted to establish specific policy measures addressing violence against children within the region. To strengthen the implementation of this regulation, the Serang City Government introduced the Integrated Community-Based Child Protection (PATBM) program. Despite the existence of this initiative, the city has continued to record a steady rise in child violence cases over the past five years. This study aims to evaluate the effectiveness of the PATBM program in addressing child violence in Serang City. Employing a quantitative research approach, the findings indicate that the PATBM program demonstrates a relatively high level of effectiveness, with an average achievement rate of 80%. However, the implementation of the program remains suboptimal. This is primarily due to limited competency among PATBM activists, indicating the need for further capacity-building and training. In addition, community participation in the program remains relatively low, which further constrains its overall effectiveness. Keywords: Program effectiveness; Child protection; Violence against children; PATBM program